2021
DOI: 10.1186/s13750-021-00226-y
|View full text |Cite
|
Sign up to set email alerts
|

How effective is ‘greening’ of urban areas in reducing human exposure to ground-level ozone concentrations, UV exposure and the ‘urban heat island effect’? An updated systematic review

Abstract: Background This review updates a systematic review published in 2010 (http://www.environmentalevidence.org/completed-reviews/how-effective-is-greening-of-urban-areas-in-reducing-human-exposure-to-ground-level-ozone-concentrations-uv-exposure-and-the-urban-heat-island-effect) which addressed the question: How effective is ‘greening’ of urban areas in reducing human exposure to ground-level ozone concentrations, UV exposure and the ‘urban heat island effect’? Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 12 publications
2
21
0
Order By: Relevance
“…In terms of air temperature differences between larger coherent green spaces (e.g., parks or cemeteries) and their built-up surroundings, our findings correspond to those of previous studies assessing temperature gradients, although, they are at the lower margin of the range of effect sizes. Bowler et al (2010) and Knight et al (2021) reported mean effect sizes of 0.94 and 0.8 °C, respectively. In our study, the largest average temperature difference of approximately 1 °C occurred in the morning between the large Friedenspark and the buffer zone of the Lene-Voigt-Park, i.e., not between the parks and their immediate surroundings.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In terms of air temperature differences between larger coherent green spaces (e.g., parks or cemeteries) and their built-up surroundings, our findings correspond to those of previous studies assessing temperature gradients, although, they are at the lower margin of the range of effect sizes. Bowler et al (2010) and Knight et al (2021) reported mean effect sizes of 0.94 and 0.8 °C, respectively. In our study, the largest average temperature difference of approximately 1 °C occurred in the morning between the large Friedenspark and the buffer zone of the Lene-Voigt-Park, i.e., not between the parks and their immediate surroundings.…”
Section: Discussionmentioning
confidence: 98%
“…In particular, urban green spaces help regulate the microclimate through shading, evapotranspiration and air flow regulation (Lehmann et al, 2014;Rahman et al, 2020;Meili et al, 2021). The potential of urban green spaces to regulate the microclimate through cooling was shown to be close to 1 °C during the daytime in parks and over 1.5 °C in urban forests with dense tree canopies compared to urban surroundings (Bowler et al, 2010;Knight et al, 2021). Dense vegetation cover, however, may reduce wind velocity and heat emission (radiative cooling) at night (Yuan et al, 2017;Knight et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The technological and organizational parameters were studied in the experiments with the thermal assessment of green buildings [3][4][5][6]. Most studies focus on the green systems assessment of the vegetation types, physical properties and thermal insulation effects of the green systems [4].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 40.9% of the articles focus on regulating services in water, 30.0% on the thermal environment, and 3.5% on air quality [3]. Green roofs showed a surface temperature cooling effect [4,5]. The effects of urban heat islands [6] and global warming have led to an increased greening of cities as a tool for urban heat island mitigation in three main climate types: hot-humid, temperate, and dry [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%